2010
DOI: 10.1074/jbc.m109.019570
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species-mediated Regulation of Mitochondrial Biogenesis in the Yeast Saccharomyces cerevisiae

Abstract: Mitochondrial biogenesis is a complex process. It necessitates the participation of both the nuclear and the mitochondrial genomes. This process is highly regulated, and mitochondrial content within a cell varies according to energy demand. In the yeast Saccharomyces cerevisiae, the cAMP pathway is involved in the regulation of mitochondrial biogenesis. An overactivation of this pathway leads to an increase in mitochondrial enzymatic content. Of the three yeast cAMP protein kinases, we have previously shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…2D. We and others have recently reported that antioxidant treatment enhances mitochondrial biogenesis (43,44). Chevtzoff and colleagues (44) have shown that the Ras/cAMP/protein kinase A pathway senses reactive oxygen species to signal to the Hap2,3,4,5 transcriptional system and regulate mitochondrial biogenesis.…”
Section: Cmc2 Is Essential For Cellular Respiration and Mitochondrialmentioning
confidence: 94%
See 1 more Smart Citation
“…2D. We and others have recently reported that antioxidant treatment enhances mitochondrial biogenesis (43,44). Chevtzoff and colleagues (44) have shown that the Ras/cAMP/protein kinase A pathway senses reactive oxygen species to signal to the Hap2,3,4,5 transcriptional system and regulate mitochondrial biogenesis.…”
Section: Cmc2 Is Essential For Cellular Respiration and Mitochondrialmentioning
confidence: 94%
“…We and others have recently reported that antioxidant treatment enhances mitochondrial biogenesis (43,44). Chevtzoff and colleagues (44) have shown that the Ras/cAMP/protein kinase A pathway senses reactive oxygen species to signal to the Hap2,3,4,5 transcriptional system and regulate mitochondrial biogenesis. We showed that increasing mitochondrial biogenesis in this way by treatment with N-acetyl-L-cysteine in a mitochondrial ATPase mutant, we were able to partially suppress a profound pleiotropic effect on COX activity (43).…”
Section: Cmc2 Is Essential For Cellular Respiration and Mitochondrialmentioning
confidence: 95%
“…We have previously shown that Hap4p amount is sensitive to oxidative stress (10). Moreover, it has been shown that a decrease in cellular phosphate potential relieves the redox pressure on the respiratory chain (35).…”
Section: Decreasing Cellular Phosphate Potential Led To Increase In Mmentioning
confidence: 99%
“…This parameter was shown to be the most relevant one to determine the cellular content in oxidative phosphorylation complexes (1,10,15,29). Mitochondrial cytochromes were measured in cells upon cellular treatment with increasing concentrations of cAMP that led to a decrease in the cellular phosphate potential.…”
Section: Decreasing Cellular Phosphate Potential Led To Increase In Mmentioning
confidence: 99%
See 1 more Smart Citation